Potentials of transanal endoscopic surgery at early rectal cancer - Yu. A. Shelygin; S. V. Chernyshov; L. P. Orlova; E. G. Rybakov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Improvement of results of organ-preserving treatment of early rectal cancer, and assessment of sensitivity and specificity of transrectal ultrasound investigation (TRUS) at these patients.Material and methods. Overall 14 patients with adenocarcinomas (uT1N0) of high or moderate degree of differentiation were selected for transanal endoscopic operation (TEO), as a basic treatment method of villous rectal tumors. Male to female ratio among investigated patients was equal (7/7). Mean tumor size was 2,6±0,8 cm (1,0–4,0 cm). The average distance from the lower pole of tumor to outer edge of anal canal and to dentate line was 7,1±1,7 cm (4,0–9,0 cm) and 4,8±1,9 cm (1,5–7,0 cm) respectively. Preoperative examination included: digital investigation of the rectum, rectoromanoscopy with biopsy, colonoscopy, TRUS, computer tomography and magnetic-resonance tomography of abdominal cavity and small pelvis.Results. The median duration of operation was 39 (25–110) minutes. Tumor-free resection edges have been obtained in all operation specimens. All tumors were removed en bloc. No postoperative morbidity was marked. Preoperative and final diagnoses coincided in all cases. At pathomorphological study adenocarcinoma at Tis stage was revealed in 3 patients (21 %), Т1 — in 10 (71%) and Т2 — in one (8%). In female patient with Т2 adenocarcinoma radical operation was executed, in the removed specimen pararectal lymph node (N1) metastasis was found out. The mean follow-up of patients was 12 (2–20) months, no signs of local tumor relapse were found.Conclusion. TEOs, having minimal morbidity level, are alternative to radical operations at early rectal cancer, however wide utilization of the method is limited by such factors, as depth of neoplasm invasion and involvement of pararectal lymph nodes. Application of TEO should be prudent. Preoperative tumor staging plays the key role.